Pengukuran Capaian Vo2max Dalam Satu Kali Sesi Cooper Test Pada Pemain Bulutangkis - Romadhona, Nurul Fajri; Waritsu, Cakra; Hasyim, Idris (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2024)
ABSTRACT Badminton is a sport that is popular win Indonesian people and is not limited by age. The indicators that a badminton player must choose are cardiorespiratory endurance and maximum oxygen consumption capacity or good Vo2max. To measure VO2max, you can use a 12-minute running test (Cooper test). This research aims to determine the effect of the Cooper test on increasing Vo2max in female badminton players at Gor Zuper Badminton Surabaya. This research uses a Quasi-Experimental research method with a one-group pre-test and post-test design. The number of samples in the research was 15 female badminton players who were members of a club. Statistical analysis used the Kolmogorov-Smirnov test. The normality test results show that the pretest and posttest have a significance level of more than 0.05, this means that the pretest and posttest data have a normal distribution. The results of the t-test data analysis show that the mean value of pre-Vo2max is 34.00 and the mean value of post-Vo2max is 37.00. The significance test with a result of 0.001 is smaller than the significance of 0.05 (0.000<0.05), meaning that there is a significant effect of 12 minutes of running training on increasing the Vo2max of female badminton players at Gor Zuper Badminton. Keywords: Cooper test, Badminton, Vo2max